2015
DOI: 10.1039/c5ra09002d
|View full text |Cite
|
Sign up to set email alerts
|

Role of multivalent Cu, oxygen vacancies and CuO nanophase in the ferromagnetic properties of ZnO:Cu thin films

Abstract: Room temperature ferromagnetism (FM) of these thin film samples are highly tuneable by the simultaneous presence of CuO nanophases and multivalent Cu and Vö concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 50 publications
0
34
0
Order By: Relevance
“…Further contribution to RTFM can come from the point defects (Zinc interstitial 'Zn i ' or vacancy of oxygen 'V O ') or the secondary phases of Cu dopants in the host lattice [49]. Hence, the observed moment is not only from a single origin, but also from V O , mixed oxidation states of Cu and CuO secondary phases [26,48]. V O cannot solely induce ferromagnetism but when it is coupled with Cu, it can incorporate ferromagnetism ordering.…”
Section: Magnetic Propertiesmentioning
confidence: 94%
See 4 more Smart Citations
“…Further contribution to RTFM can come from the point defects (Zinc interstitial 'Zn i ' or vacancy of oxygen 'V O ') or the secondary phases of Cu dopants in the host lattice [49]. Hence, the observed moment is not only from a single origin, but also from V O , mixed oxidation states of Cu and CuO secondary phases [26,48]. V O cannot solely induce ferromagnetism but when it is coupled with Cu, it can incorporate ferromagnetism ordering.…”
Section: Magnetic Propertiesmentioning
confidence: 94%
“…3a) Observed RTFM in the CZO is due to the interaction among the dopant Cu impurities as well as the native defect states present in ZnO [2]. Since delocalized electrons in Cu ions mediated the RTFM [26,47], it suggests that the ferromagnetism is originated from carrier-induced exchange couplings in the Cu dopants. Xia et al [44] reported that the exchange interaction among the conductive electrons and the local spin-polarized electrons induces RTFM as proposed in Ruderman-Kittel-Kasuya-Yosida (RKKY) theory.…”
Section: Magnetic Propertiesmentioning
confidence: 99%
See 3 more Smart Citations